Formalismo e finalidade na moral kantiana : a destinação da razão na fundamentação da metafísica dos costumes - Rissi, João Paulo (2016)
In the Groundwork of the Metaphysics of Morals, Kant seeks to support human action by a rational principle (formal) and not by the search for an order previously established outside the very principle. Therefore, for Kant, human action is good to be determined only by the rational principle, regardless, so, the realization of any order previously determined. It is concluded, therefore, that in Kantian moral which gives moral value to action is our intention to act in accordance which universal principles that can apply to all men, and not the realization of the end pursued by the will. However, even that assign moral value only the intention of action liable of universalization, Kant would, therefore, removed from his moral philosophy once and for all the possibility of some ultimate end? It is important to note that the very GMM Kant introduces the concept of Bestimmung. This concept states that the reason also has a destination, understood as ultimate goal: the production of a good will. Destination, at least output, suggests to us that eventually there would be a kind of end point of reason, which is nothing more than the production of their own good will. So how can we think that point, without ignoring, of course, that is the intention of the action which gives moral value? Kant, having founded his moral philosophy on the intention of the agent that determines its action by a rational formal principle, would have thus prevented any opening to a teleological theory in his moral philosophy? It is intended, based on these issues and their consequences, show not only that Kant did not rule out his practical philosophy a possible reading finalist, but also made it possible to think of a congruence between formalism and purpose.